Design of wide band SIW based Reflective Mode FSS with Angular Stability for X-band application - Saranya Madheswaran; Rajeshkumar Venkatesan (Results in Engineering, 2025)
This paper presents a design of Substrate Integrated Waveguide (SIW) based reflective mode Frequency Selective Surface (FSS) that operates in wide-band tailored for X-band applications. The design is implemented on FR4 substrate, which has a dielectric constant (εr) of 4.3, chosen for its favorable electrical properties and compatibility with the intended frequency range. Regarding physical dimensions, FSS is highly compact, featuring unit cell dimensions of 11 × 11 × 1.57 mm3, making it suitable for space-constrained applications. The SIW-based FSS structure gives a wide bandwidth of 9.05–14.50 GHz with a relative bandwidth of 46.28 %. To validate the design, a comprehensive equivalent circuit model is implemented, providing a theoretical foundation for the FSS performance. Furthermore, hardware fabrication of the proposed design is undertaken to verify the model's predictions empirically. The experimental results support the theoretical findings, demonstrating the FSS effectiveness in real-world scenarios. This FSS design is optimized for critical applications in radar and electromagnetic shielding within the X-band frequency range, offering a significant advancement in developing high-performance, compact, and wideband FSS technologies.